The Mediation Role of Job Satisfaction on Employee Performance Based on Organizational Citizenship Behavior and Organizational Support - Setyadi, Setyadi; Widayati, Tri (Untag Business and Accounting Review, 2025)
This research aims to analyze the effect of organizational citizenship behavior (OCB) and organizational support on employee performance through job satisfaction as an intervening variable.Â  The population used in this research was all employees in the Wiradesa District of Pekalongan Regency, Central Java,with 165 employees. The sample size is 116 employees selected with Slovinâ€™s formula by proportional random sampling. Structural Equation Modeling-Partial Least Squares (SEM-PLS) has been chosenas a data analysis technique.The results show that OCB and organizational support have a positive and significant effect on job satisfaction and employee performance. Job satisfaction also has a significant effect on employee performance. The result of the research also shows that job satisfaction has a mediating role in OCB and organizational support toward employee performance.This study's theoretical implication is to validate the important role of OCB factors in developing job satisfaction and driving employee performance in an organization